Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Review - Exercises - Page 134: 38



Work Step by Step

$(x+2)^{2}-7(x+2)+6$ Let $x+2$ be equal to $u$: If $x+2=u$, then $(x+2)^{2}=u^{2}$. Rewrite this expression using the new variable $u$: $u^{2}-7u+6=...$ Factor this expression: $...=(u-6)(u-1)=...$ Substitute $u$ back to $x+2$ and simplify: $...=(x+2-6)(x+2-1)=(x-4)(x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.